Study Analysis of the Potential of T-Shirt Business Based on the Osing Language in Banyuwangi - Indah Wahyu Ferawati (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2022)
The condition of Banyuwangi, which has begun to develop its tourist attraction, has made many Banyuwangi residents use it for business, not only as food souvenirs but also typical Banyuwangi t-shirts. One of the innovations that can be done in the T-Shirt business is to implement elements of local wisdom (words in the Osing language). To find out the potential of the T-Shirt business based on foreign language words, it is necessary to conduct research studies through analytical studies to determine the extent of consumer response. This research is a descriptive analysis research using 100 respondents who are divided into two categories, namely the category of adolescents (17-25 years) and adults (26-35 years). Overall, the accumulation of data from respondents regarding the interest in buying T-Shirt products based on foreign language words is 71% agree to buy, 18% do not, and 11% are undecided between buying the product or not. The results of this analytical research can be taken into consideration by T-Shirt business actors in Banyuwangi to determine the type of product and their target market. To obtain study results with high validity, it is necessary to conduct further research with a larger scale of respondents.